PENGARUH LINTAS BUDAYA PADA PEMASARAN INTERNASIONAL DENGAN PENDEKATAN PERILAKU KONSUMEN - Endy Gunanto; Yenni Kurnia Gusti (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2014)
In this article we present a conceptual of the effect of cross culture on consumer behavior incorporating the impact of globalization. This conceptual idea shows that culture inûuences various domains of consumer behavior directly as well as through international organization to implement marketing strategy. The conceptual identify several factors such as norm and value in the community, several variables and also depicts the impact of other environmental factors and marketing strategy elements on consumer behavior. We also identify categories of consumer culture orientation resulting from globalization. Highlights of each of the several other articles included in this special issue in Asia region. We conclude with the contributions of the articles in terms of the consumer cultural orientations and identify directions for future research.